(untitled) (Baghdad Science Journal, 2025)
This study aims to predict the organic pollution produced from the presence of some polycyclic aromatic hydrocarbons (PAHs) and determination it’s concentrations (µg/L , ppb) in Tigris river water by a collection twenty-seven water samples from a selected three stations with nine sampling sites and three depths of water (5 cm , 2 m and 4 m) each site for 4.6 km distance of a geographic studied area which is located between the ( Al-Senak and AL-Sarrafiah bridges ) at Baghdad city – Iraq on May, 2012. The geographic location was determined with a Global Positioning System (GPS) and Geographic Information System (GIS) software program. The concentrations of fourteen components (PAHs) were performed using the reverse phase of high performance liquid chromatography (RP-HPLC) technique. Samples were chemically treated using liquid-liquid extraction method , filtered , extracted , dried , evaporated and pre-concentrated in order to be ready for analysis . The determined concentrations of (PAHs) for the studied area did exceed the criteria values proposed by the International Environmental Organizations like American Environment Protection Agency (U.S-EPA) and British Health Agency (BHA) . The results were showed that the maximum values of the total concentrations (PAHs) were found to be 228 µg/L (5 cm depth , site F, Medicine city station , Al-Resafa bank) , 192.1 µg/L (2 m depth , site D , Medicine city station , Al-Karkh bank) and 80.1 µg/L (4 m depth , site D , Medicine city station , Al-Karkh bank) , while the minimum values were found to be be 51.2 µg/L (5 cm depth , site I, Al-Sarrafia bridge station , Al-Resafa bank) , 33.4 µg/L (2 m depth , site G , Al-Sarrafia bridge station , Al-Karkh bank) and 4.8 µg/L (4 m depth , site G , Al-Sarrafia bridge station , Al-Karkh bank) .